Three new species of genus Theages Walker, 1855 (Lepidoptera: Erebidae: Arctiini) from Peru and Ecuador - Grados, Juan (2018)
Three new species of the genus Theages Walker, 1855 (Lepidoptera: Erebidae: Arctiini) occurring in the montane forests of the Andes of Peru and Ecuador are described and illustrated.